2012
DOI: 10.1590/s0104-11692012000600014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biomechanical parameters extracted from anorectal manometry of fecally-continent and incontinent patients

Abstract: Objective: to evaluate the average resulting area from the Pressure x Time curves resulting from the manometric anorectal exam and compare it with the support capacity of voluntary squeeze.Materials and Methods: the data set was represented by data from 11 exams from continent patients and eight exams from patients with grade III fecal incontinence. Análisis de parámetros biomecánicos extraídos de la manometría rectoanal de pacientes con continencia e incontinencia fecalObjetivo: evaluar el área media resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is an important examination and used in research centers, clinics or specialized hospitals searching for anorectal disorders 22 , 24 ; it may suggest the diagnosis and guide the management 15 , 22 , 24 . This anorectal physiology test has a well-established impact in the evaluation of the abnormalities of the anorectal sphincter function and anal coordination during defecation 1 , 7 , 10 , 18 , 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important examination and used in research centers, clinics or specialized hospitals searching for anorectal disorders 22 , 24 ; it may suggest the diagnosis and guide the management 15 , 22 , 24 . This anorectal physiology test has a well-established impact in the evaluation of the abnormalities of the anorectal sphincter function and anal coordination during defecation 1 , 7 , 10 , 18 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of patients with symptoms of anal incontinence may present normal manometric values 16 , 19 . Anorectal manometry clinical usefulness may be limited by the variation of types of devices used in the market, due to a deficiency of standardized protocols in different facilities and what are considered the normal parameters in healthy individuals without pelvic floor disorders 7 , 13 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had been reported in modeling complex elasticity properties, and biomechanical models are widely used due to the high accuracy achieved [9] , [10] . However, these models are complicated [11] , [12] , and the accuracy obtained relies on the accuracy of tissue geometry modeling and measurements of forces and deformations, as well as the rich excitation of material regimes [8] . Another commonly used model is the mass-spring model.…”
Section: Introductionmentioning
confidence: 99%